Case of an anti‐N‐methyl‐d‐aspartate receptor encephalitis patient responding to cyclophosphamide with significant brain volume recovery. Issue 4 (29th May 2020) - Ashida, Shinji; Tanaka, Eijirou; Ogura, Shiori; Maezono, Keiko; Nagakane, Yoshinari
Abstract: Background: Anti‐ N ‐methyl‐d ‐aspartate receptor (NMDAR) encephalitis is a severe form of limbic encephalitis. Some patients with anti‐NMDAR encephalitis do not respond to standard immunotherapy, resulting in poor outcomes. Case presentation: We report an 18‐year‐old female patient with anti‐NMDAR encephalitis, without a tumor, who showed a marked response to cyclophosphamide. She was admitted due to a 1‐month history of headache, psychiatric symptoms, and consciousness disturbance. Despite administering first‐line immunotherapy, including steroid pulse, intravenous immunoglobulin, and plasma exchange, she developed orofacial dyskinesia, central hypoventilation, and status epilepticus. Involuntary movements and seizure began to decrease only after the administration of cyclophosphamide (CPM), and she showed gradual improvement over the next 5 years. In addition, significant recovery from brain atrophy was observed on follow‐up MRI. Conclusions: Cyclophosphamide should be considered for nonresponders to first‐line immunotherapy. Abstract : We report an 18‐year‐old female patient with anti‐NMDAR encephalitis, who showed a marked response to cyclophosphamide (CPM). Significant recovery from brain atrophy was observed on follow‐up MRI parallel with neurological improvement over 5 years after CPM.